24 Unravelling Genomic Regions with Transmission Ratio Distortion: Identification of Candidate Lethal Alleles in Cattle. (10th April 2018) - Id-Lahoucine, S; Casellas, J; Fonseca, P; Miglior, F; Sargolzaei, M; Brito, L F; Miller, S P; Schenkel, F S; Asselstine, V H; Chesnais, J P; Lohuis, M; Medrano, J F; et al.
Abstract: Transmission ratio distortion (TRD) is the deviation from the expected Mendelian inheritance of alleles from heterozygous parents. This phenomenon has been reported in a broad range of organisms and can be caused by various biological mechanisms including meiotic drive, embryo or fetal failure, germline selection, gametic competition, imprint resetting error and differential survival of offspring. Within this context, we investigated TRD in cattle aiming to identify genomic regions showing altered deviations in segregation that could contain potential causal mutations directly affecting economically important traits, such as reproduction. A Bayesian approach was implemented in order to uncover TRD across the whole genome using SNP-by-SNP and haplotypes of 2-SNP sliding windows using 79, 238 genotyped trios of Holstein. From a total of 44, 369 autosomal SNP, 942 were significantly detected with TRD that exceeded a Bayes factor (BF) ≥ 10 (strong evidence) and 408 with BF ≥ 100 (decisive evidence) from SNP-by-SNP analyses. The number of SNP with parent-unspecific TRD were 270 whereas 393 and 271 SNP were detected as either sire- or dam-TRD, respectively. By using the approximate empirical null distribution of TRD, results potentially generated by chance were discarded, resulting in 555, 307 and 92 SNP significantly detected with a probability of error of 5%, 1% and 0.1%, respectively. From the SNP-by-SNP approach, regions with moderate-to-high |TRD| (≥ 0.15) were less polymorphic (minor allele frequency, MAF < 0.027), providing evidence of TRD selection and unravelling rare variants as candidate lethal alleles. In contrast, slightly more polymorphic regions with moderate-to-high |TRD| were identified by the haplotype approach (MAF ~ 0.045). The number of regions identified by haplotype approach after correction (at 0.1% probability of error) were 1, 047, 421 and 683 for overall, sire- and dam-TRD, respectively. The preliminary functional analysis of detected regions with TRD identified positional genes associated with regulation of embryonic development. Moreover, the identification of alleles with TRD in chromosomal regions around haplotypes well known to be associated with recessive disorders in Holstein or affecting fertility traits in other cattle breeds highlighted important biological implications of TRD. In conclusion, the prevalence of TRD was extended across the whole genome and an in-depth deeper study of these candidate regions and alleles will be further investigated to better understand this phenomenon in cattle.